Presentación: Acercamiento al Mundo Andino desde la Tarea Eclesial - Iguíñiz Echeverría, Javier (1984)
In the first part of this issue of ALLPANCHIS we have brought together a set of articles of a different nature from the usual ones. John Paul II's visit has motivated us to ask some of the pastoral agents of the Andean world for a written expression of their experience. As such, these works, under the title "Approach to the Andean world from the ecclesial task" do not constitute studies of an academic-intellectual nature. They intend to be expressions of those who live, above all, among the peasantry to attend to their needs from God and to reflect critically on their reality on their Andean social reality, based on the ethical demands coming from the Gospel of Christ. Hundreds and thousands of ways of looking at reality arise from the hundreds and thousands of religious and lay pastoral agents who live with the poor of our poorest walk. The works presented show, for this reason, a few of those approaches where the feeling of solidarity translates into a silent action, little given to writing and academic research.